Extracción reactiva en procesos controlados por la cinética (2016)
Stage to stage flash algorithm (MSEO) is extended to solve kinetically controlled reactive extraction processes. The Non-Conventional Separation Processes research group developed the algorithm based on the introduction of a key parameter called Damkóhler number, it allows to extend such an algorithm to model kinetically controlled processes. The algorithm is suited to solve several configurations in an extraction process. Parallel and countercourrent operations are presented under isothermal condition and constant or variable Damkóhler number. Two application examples are presented, butyl acetate and amyl acetate reactive extraction processes.